Monitoramento da gestão ambiental municipal nas capitais do nordeste brasileiro - Santos, Carina Angélica dos (2019)
Environmental management is a set of policies, programs and practices carried out through planned and articulated actions, considered systemic, and involves all decision-making instances of society in the various spheres of competence. Such a conception needs an institutional arrangement that determines its responsibility and participation. Therefore, shared and decentralized management should be practiced, placing the municipality as a participant in local environmental management, dealing with the environmental problems in question. Thus, it is essential to know the structure, legislation, human resources, legal instruments, among others, to understand how the system will work. From these aspects, this study aimed to analyze the municipal environmental management and propose a monitoring methodology that would point out the advances and weaknesses of environmental actions in the capitals of the Northeast of Brazil. Three chapters resulted from this purpose: Chapter 1 aimed to analyze how environmental public policies contribute to municipal environmental management through reflection on the environment and the municipalities in the constitution, public policies and environmental management instruments. Then, in chapter 2, a bibliometric analysis of academic studies, between theses and dissertations, related to the theme was performed in order to verify the contributions made by these investigations to municipal environmental management. Finally, chapter 3 aimed to present a methodology for monitoring the municipal environmental management that pointed out the advances and weaknesses of environmental actions in the capitals of the Brazilian Northeast. The methodological procedure was done through a descriptive and quantitative-qualitative approach, based on laws, articles, books, theses and dissertations, data from MUNIC / IBGE. As a result, it was firstly found that the evolution of environmental public policies contributed to municipal environmental management by meeting the demands and being able to understand the process of planning, control and supervision of environmental actions. Secondly, it found that academic studies have contributed to subsidizing environmental management by addressing various topics such as: conditioning factors of management, integrated system, public policy, indices and indicators and social participation and environmental program, responding to local environmental demands and developing a positive agenda to assist in environmental policy, planning and management. Finally, by analyzing the historical series of environmental institutional capacity for Brazil, Northeast Regions and Capitals, using data from the Municipal Basic Information Survey (MUNIC), a ranking was made of the capitals of the Northeast. A consolidated arrangement for environmental management was detected highlighting the advance in management and a weakness in human resources. Thus, it is concluded that the academic studies and analyzes of the historical series allow to monitor the municipal environmental management.